مشروع اليونسكو لتشغيل نظام الي متكامل مفتوح المصدر بمكتبات الجامعات السودانية 2012: جامعة السودان - جامعة الخرطوم - جامعة النيلين - ا. عبد الرزاق محمود ابراهيم الحاج (White Nile Journal for Studies and Research, 2019)
Integrated library automation systems considered as one of the most effective tools, through which libraries could achieve their desired objectives. However, most Sudanese universities suffer from lack of financial resources required to obtain these systems To overcome this obstacle, the Sudan University of Science and Technology, with the support of UNESCO, initiated the development of university libraries in Sudan through the operation of an integrated, open source systems So, the open-source system (KOHA) was operated in the universities of the environment. Sudan, Nyalin and Khartoum The study looks at the importance of adopting open source systems and their compatibility with library The study aims to identify the criteria of selecting and operating open source systems. In addition, the study aims to identify the impact of this selection in developing the performance of tasks, duties and services commensurate with the requirements of the information technology era. The researcher used the inductive analytical descriptive method and the historical approach in the study The results of the study were the following: The choice of the open-source Koha system was based on meeting international standards. The recommendation of the study is, encouraging the adoption of projects for the operation of the open source integrated library systems in the libraries of Sudanese universities.